Empirical study on the work-life balance issues of chef at supervisory level in hotels of Delhi - Khanna, Kavita; Bali, Paresh (International research journal of management, IT and social sciences, 2017)
The objective of the research was to find out work-life balance issues for chefs at the supervisory level in Hotels of Delhi. The supervisory level chefs are very critical to fulfilling the requirement of the smooth operations of the different section of the kitchen or food production department. Supervisors have to monitor, guide and motivate the operative staff of any department or process; this becomes more important if it is food production department of a hotel. The objective of the study was to find out whether there exists a healthy work life balance in lives of supervisory chefs engaged in hotels of Delhi. The paper also tries to evaluate the work life balance on the four dimensions of work life balance namely quality time, involvement, satisfaction, and health. The study tries to analyze and identify the probable causes of work life imbalance and expected solutions for the improvement of work life balance. The author had devised a questionnaire to gather the data from the respondents, which included a set of statement on which participants agreement or disagreement was recorded.